Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Pengelolaan Keuangan di Cafe And Resto Juragan Tepi Sawah - Sri Wahyuni putri; Samsul Bachri; Duriani Duriani (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The purpose of this study is to examine the influence of financial literacy and lifestyle on financial management at Cafe and Resto Juragan Tepi Sawah. This research adopts a quantitative method. The population consists of 35 respondents divided into two groups management and employ-es all of whom were included as the sample. Data were collected through a questionnaire using a Likert scale and analyzed using IBM SPSS 25. Hypothesis testing was conducted through multiple linear regression analysis. The results show that financial literacy and lifestyle have a significant effect on financial management at the cafe. The implications of these findings highlight the importance of improving financial literacy among culinary business actors to optimize financial management, as well as the need for greater awareness of planned and prudent lifestyle choices in managing business finances. This study provides insights for cafe and restaurant owners and managers to improve financial habits that support business sustainability.